(untitled) (Research, Society and Development, 2020)
Environmental Education is an educational process aimed at awakening individual and collective concerns in the general public about environmental issues. It should provide clear and objective access to information and contribute to the development of a critical awareness of today’s environmental problems. The purpose of this article is to map the undergraduate courses in Environmental Education in Private Higher Education Institutions in São Paulo State. This has involved a survey and in-depth analysis of the curriculum of 12 institutions, totaling 593 courses, covering the different areas of knowledge and types of degree. Of the courses analyzed, 36.4% contained subjects related to Environmental Education. The analysis of types of degree indicated that Environmental Education is more often included in Teaching Diploma ("Licenciatura") courses (58.7%), while in the BA degree and Short Courses the percentage was 33.8%. This is an interesting and very important fact, since the Teaching Diploma trains people who are going to disseminate knowledge and ideas in schools.